Fixed Points of Multivalued Nonself Almost Contractions - Maryam A. Alghamdi; Vasile Berinde; Naseer Shahzad (Journal of Applied Mathematics)
We consider multivalued nonself-weak contractions on convex metric spaces and establish the existence of a fixed point of such mappings. Presented theorem generalizes results of M. Berinde and V. Berinde (2007), Assad and Kirk (1972), and many others existing in the literature.